STRATEGI GURU DALAM MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ERA MILENIAL DI MTS NEGERI BATU - Anis Setyowati (VICRATINA, 2022)
AbstrakIn this research, case studies and qualitative approaches are used. This study aims to describe learning planning, teaching practices and assessment of Islamic religious education at MTs Negeri Batu. In this study, the researcher functions as a tool as well as data collector. The results of the research are 1) curriculum planning carried out by PAI teachers at TMs Negeri Batu is in accordance with the learning planning method (RPP), teachers use skills-based strategies and the skill level of the students they occupy. by different students, they use what the teacher uses. planning to score consistently different learning outcomes; 2) The implementation of teaching staff led by teachers is divided into three activities: preparatory activities, basic activities and final activities; 3) Evaluation of Islamic religiouseeducationslearningsat MTs Negeri Batu can be grouped into three aspects, namely cognitive, affective and psychological aspects.Kata Kunci: Strategi, Pembelajaran, Pendidikan Agama Islam,Era Milenial, MTs Negeri Batu